Trajectories of Single- or Multiple-Substance Use in a Population Representative Sample of Adolescents: Association with Substance-Related and Psychosocial Problems at Age 17 - Rene Carbonneau; Frank Vitaro; Mara Brendgen; Michel Boivin; Sylvana M. Côté; Richard E. Tremblay (Brain Sciences)
Background: Research is limited regarding the relationship between adolescent substance use and polysubstance use (SU/PSU) as well as their outcomes later in adolescence, while accounting for early risk factors. This study explored substance-related and psychosocial outcomes at age 17 associated with SU/PSU developmental trajectories in a population-representative cohort from Quebec, Canada (N = 1593; 48.4% male), while controlling for preadolescent individual, familial, and social risk factors. SU/PSU included concurrent use of alcohol (AL), cannabis (CA), and other illicit drugs (ODs). Methods: Self-reported substance use data were collected at ages 12, 13, 15, and 17. Latent growth modeling identified five trajectories: Non-Users (12.8%) and four SU/PSU classes (5.8–37.5%) with varying severity based on onset, frequency, and substance type. Multinomial regression, using non-users as the reference group, assessed trajectory associations with age-17 outcomes. Individual, familial, and social risk factors assessed at ages 10–12 served as control variables. Results: Adolescents in high-risk SU/PSU classes showed the most negative substance-related and psychosocial outcomes compared to non-users and lower-risk SU/PSU classes. Lower-risk SU/PSU classes showed higher maladjustment than non-users. Conclusions: The findings highlight a dose–response relationship between SU/PSU trajectories and late-adolescent outcomes, independent of preadolescent risk factors. Results emphasize the importance of longitudinal studies that incorporate multiple substances to better capture the complexity of teenagers’ involvement in substance use throughout adolescence.